Text, Law, and Riot: The Coloniality of Religious Offense in Late Colonial Burma - Phyo Win Latt (Elkuator Research and Publication, 2026)
This article investigates the 1938 Indo-Burman riots—an eruption of communal violence that occurred a decade before Burma’s independence—through the prism of Moulvi-hnint-Yogi Awada Sadan, a composite polemical text that became central to legal prosecution, political mobilization, and sectarian unrest. Rather than reducing the conflict to a simplistic narrative of “religious insult,” the study reconstructs the book’s multivocal authorship, multireligious composition, and its mediated circulation across pressrooms, monastic institutions, and colonial legal forums. The analysis foregrounds the coloniality of offence, examining how juridical categories such as “malicious intent” and “religious offence” were embedded within colonial legal frameworks, enabling the state to adjudicate symbolic injury while deflecting responsibility for structural violence. By tracing the trajectory from textual controversy to riot, trial, and legislative response, the article demonstrates how polemical disputes were instrumentalized to forge regulatory regimes that entrenched communal divisions. It concludes by exploring the afterlives of the text in contemporary Myanmar, where its memory continues to inform contentious debates around religion, identity, and legal governance.